CHEMICAL AND CARBON ISOTOPIC FRACTIONATIONS OF GASEOUS HYDROCARBONS DURING ABIOGENIC OXIDATION - Pan C.; Yu L.; Liu J.; Fu J. (My University, 2006)
The variations of chemical and carbon isotopic compositions in gaseous hydrocarbons upon abiogenic oxidation by sulfates, hematite and both in laboratory studies were clearly demonstrated through a unique two-step experimental approach. In the first step, a large number of small gold capsules containing gaseous hydrocarbons were prepared by kerogen pyrolysis experiments, which were conducted under the same condition (450 °C and 50 MPa for 72 h) using the same kerogen. The analytical results demonstrated that the chemical and carbon isotopic compositions of gases were almost identical among the capsules. In the second step, each of these gaseous hydrocarbon-bearing capsules, along with mineral oxidant (hematite, or magnesium sulfate heptahydrate, or both) and deionized water (15% of the amount of the oxidant), was placed into a large gold capsule. After welding (sealing), the small gaseous hydrocarbon-bearing capsule was forced to leak while the large capsule remained undamaged by compressing the large capsule from the outside at the position where this small capsule was located. Then, these large capsules containing gas and mineral reactants were heated isothermally at 350 °C and 50 MPa for 72, 144, 216 and 288 h, respectively. The results of the oxidation experiments with increasing heating time can be outlined as follows: (1) the amount of methane remained almost unchanged in the experiments using hematite and the mixed oxidants (hematite + MgSO4) while it increased substantially in the experiment using MgSO4 after 72 h, indicating methane was one of the final products of C2+ oxidation; (2) the amounts of C2-C5 hydrocarbons decreased consistently and more rapidly in the experiment using MgSO4 than that using hematite and the mixed oxidants; (3) the oxidation rates of gas hydrocarbons increased with increasing carbon number of hydrocarbons; (4) the oxidation rates of i-butane and i-pentane were substantially higher than those of the corresponding n-butane and n-pentane; (5) the amount of H2S increased substantially in the experiment using MgSO4, whereas it was below the detection level in the experiments using hematite and the mixed oxidants; (6) the δ13C values of C1-C5 hydrocarbons became less negative and the isotopic fractionation extent increased with increasing carbon number of hydrocarbons and oxidation extent; (7) carbon isotopic fractionation factor α (k12/k13) decreased with increasing oxidation rate of gas hydrocarbons; and (8) the rate of thermochemical sulfate reduction (TSR) was strongly dependent upon the presence and concentrations of H2S. © 2006 Elsevier B.V. All rights reserved.
Keywords: ABIOGENIC OXIDATION; GASEOUS HYDROCARBONS; THEMOCHEMICAL SULFATE REDUCTION (TSR)